Genetic characterization of Indian little millet (Panicum sumatrense) genotypes using random amplified polymorphic DNA markers - Tiwari, Neelam; Tiwari, Sharad; Tripathi, Niraj (Agriculture and Natural Resources, 2018)
Initially, 60 primers were screened among 32 genotypes of little millet (Panicum sumatrense), from which 36 primers were selected on the basis of a sharp and clear banding pattern for final random amplified polymorphic DNA (RAPD) analysis. The PCR reaction was carried out using a single decamer primer at a time. In total, 175 RAPD marker loci were amplified of which 155 were polymorphic (88.58%). The band size of amplified markers was in the range 100-1900 bp. Ten bands were the maximum scored (for primer OPH-19) whereas two bands were the minimum scored (for primer OPC-13). On average, 4.86 bands per primer and 4.31 polymorphic bands per primer were recorded. The polymorphism information content ranged from 0.102 (OPAI-01) to 0.517 (OPE-04). A dendrogram divided the genotypes into two major and further into sub-groups according to their collection center geographical regions. This was the first report on molecular diversity analysis of a large collection of little millet germplasm. Diverse genotypes may be used in breeding programmes for P. sumatrense improvement.